The Effect of Applying the International Guidelines for Clean Surgery on Infection Control of Patient’s Close Intimate Environments - Abdulkahar, Ismaeil M.; Mohammed, Haider N.; Mansour, Sabeeha A. (Science Journal of University of Zakho, 2017)
Surgical site infections are the most common cause of hospital acquired nosocomial infections. To evaluate the effects of applying and following the international standard guidelines for clean surgery on the final infection control in operation theatres, a comparative study was designed and carried out during the period from May 2014 to February 2015, at two operating theatres, the general surgical and the gynaecological theatre at Azadi teaching hospital – Duhok city – Kurdistan region. A total number of 492 samples (swabs and settles plate) were taken from different sites of intimate contact with the patients and were divided into two parts, pre (part I) and post (part II) samples. They were taken in a periodic day to day, and collected periodically three days of the week (Saturday -Monday- Wednesday) for a period of one month. Swabs were taken from different places were streaked on Blood and Mac-Conkey agar plates and incubated at 37°C under aerobic conditions for 24 hours. After incubation, the bacterial colonies were counted and diagnosed by Phoenix. The concentration of bacteria was expressed as colony forming units. The rates of bacterial contamination in places of close contact with patients of both theatres before the application of the WHO guidelines were as following: out of 348 samples collected from the surgical theatre in the first part; 105 (30.1%) showed significant growth in comparison to 32/144(22.2%) that showed significant growth from the gynaecological theatre, while all samples in part II from the surgical theatre showed no significant growth that 100%, in comparison to141/144(97.92%) in the gynaecological theatre in the second part after application of the WHO guidelines. As a conclusion there are 3 factors which have an effect on the result of surgical site infections namely patients, staff and environmental factors. The environmental factors have the greatest impact which are indirectly related to the degree of application of WHO standards of operation theaters.